Spectrally efficient OFDM system and its possible use in cognitive radios - Kwek, Liren Raphael. (2009)
Orthogonal frequency-division multiplexing (OFDM) is generally known as an effective technique for high bit rate applications such as digital audio broadcasting (DAB), digital video broadcasting (DVB), digital high-definition television (HDTV) broadcasting and wireless local area networks (Wireless LANs), since it can prevent intersymbol interference (ISI) by inserting a guard interval and can mitigate frequency selectivity of a multipath channel using a simple one-tap equalizer. [1] Conventional OFDM systems transform information symbol blocks and then insert redundancy in the form of either cyclic prefix (CP) or zero padding (ZP). The redundancy due to the CP/ZP causes reduction in the code rate of the communication system. The loss in the code rate may be around 10–25%. The loss is more when the finite impulse response (FIR) channel order is comparable with the number of subcarriers used in the OFDM system. [2] We are concerned with the study of new methods such that this loss in spectral efficiency is minimized /reduced while maintaining the same QOS (quality of service). This is achieved at a moderated increase in complexity. Such an OFDM system can be possibly used in the context of a cognitive radio. In cognitive radio, the secondary users can sense the spectrum and when the primary users are silent, they borrow the licensed bands of the primary users. The secondary users therefore have opportunistic access of the spectrum and should make the most of it when available. Hence a spectrally efficient OFDM system can be used for a secondary user to improve system performance.